A LEADER-térségek fejlődését akadályozó tényezők értékelése és a helyi akciócsoportok szerepe a helyi fejlődésben - Kis, Krisztián (Közép-Európai Közlemények, 2011)
During the 2007–2013 programming period in Hungary 96 Local Action Groups (LAGs) have got the opportunity to contribute to the local development process using LEADER approach, based on the concept of endogenous development. The nationwide survey carried out among Hungarian LAGs indicates that human resources (rural people and their communities) are not only factors of rural economies, but also areas of improvement. The LAGs are basic institutions of implementing the LEADER Programme, and according to their proactive operations they play a crucial role in local rural develeopment. Through their func)tions and activities the LAGs generate synergy effect, which actually means the positive contribu)tion of LAGs to the territorial processes. In this way the synergy is the added value of the LAGs’ operation, a joint effect, which can be realize through improving relations between the stakeholders.